Relationship between Vitamin C and Length of Hospital Stay for Covid-19 Patients with Comorbidities - Budiyanti Wiboworini; Amelya Augusthina Ayusari; Risalina Myrtha; Dwi Rahayu; Widardo Widardo; Yulia Lanti; Amalina Shabrina; Joko Sudarsono; Sutartinah Sri Handayani; Graciella Angelica Lucas (Faculty of Medicine, Universitas Padjadjaran, 2022)
Covid-19 patients with comorbidities, such as hypertension, diabetes, and respiratory diseases, have a higher risk for severe disease and mortality compared to patients without comorbidities. Some data shows that the administration of high dose vitamin C (1–2 g/day) can reduce the amount of the inflammatory mediators and shorten the length of hospital stay. This study aimed to determine the relationship between vitamin C administration and of length of hospital stay for Covid-19 patients with comorbidities. This study was a retrospective observational study on consecutively sampled medical record data of UNS Hospital patients from July 2020 to January 2021. A total of 78 patient medical records were included of this study. The inclusion criteria were all medical records of patients who suffered from Covid-19 with comorbidities admitted to the hospital while the exclusion criteria were medical records of patients who did not get oral or intravenous vitamin C. The chi-square bivariate test was used to determine the relationship between the administration of vitamin C and the length of hospital stay for Covid-19 patients with comorbidities. Of the 78 subjects only 52 subjects were included in the statistical analysis. Medical records were divided into two groups: group 1, that consisted of medical records of patient who received more than 1,000 mg Vitamin C, and group 2, who received less than 1,000 mg Vitamin C. Results demonstrated that the administration of high dose vitamin C of more than 1,000 mg was not associated with the length of hospital stay (p=0.677). Thus, high dose of vitamin C is not associated with the length of hospital stay for Covid-19 patients with comorbidities, such as hypertension, diabetes, and respiratory disease.